The Church and the Law in the Early Middle Ages - McKitterick, Rosamond (Studies in church history, 2020)
Two case studies from eighth-century Rome, recorded in the early medieval history of the popes known as the Liber pontificalis, serve to introduce both the problems of the relations between secular or public and ecclesiastical or canon law in early medieval Rome and the development of early medieval canon law more generally. The Synod of Rome in 769 was convened by Pope Stephen III some months after his election in order to justify the deposition of his immediate predecessor, Pope Constantine II (767-8). Stephen's successor, Pope Hadrian, subsequently presided over a murder investigation involving Stephen's supporters. The murders and the legal process they precipitated form the bulk of the discussion. The article explores the immediate implications of both the murders and the convening of the Synod of Rome, together with the references to law-making and decree-giving by the pope embedded in the historical narrative of the Liber pontificalis, as well as the possible role of the Liber pontificalis itself in bolstering the imaginative and historical understanding of papal and synodal authority. The wider legal or procedural knowledge invoked and the development of both canon law and papal authority in the early Middle Ages are addressed. The general categories within which most scholars have been working hitherto mask the questions about the complicated and still insufficiently understood status and function of early medieval manuscript compilations of secular and canon law, and about the authority and applicability of the texts they contain.